1986
DOI: 10.1104/pp.82.2.339
|View full text |Cite
|
Sign up to set email alerts
|

The Occurrence of Abscisic Acid and Abscisyl-β-d-Glucopyranoside in Developing and Mature Citrus Fruit as Determined by Enzyme Immunoassay

Abstract: The contents of (+)-cis-abscisic acid (ABA) and alkaline-hydrolyzable ABA-conjugate(s) ABA and water-soluble ABA-conjugates are important components of the growth inhibitor complex of many plants (1). The levels of these compounds have been reported to increase during fruit maturation and this observation has given rise to speculation on their role in fruit ripening and other related developmental phenomena (16). Increases in ABA and ABA-conjugates in citrus fruit have been related to exocarp senescence and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
24
0

Year Published

1986
1986
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 22 publications
4
24
0
Order By: Relevance
“…From this point of view, the conversion from GA to Me-GA might be a part of a regulatory network for GA-ABA homeostasis during seed maturation and germination. The conjugation of phytohormones with methyl groups, sugars and amino acids has been proven as an effective way to regulate the phytohormones homeostasis in planta (Cohen and Bandurski 1982;Harris and Dugger 1986;Jackson et al 2001;Hou et al 2003;Qin et al 2005). For auxins, conjugates with sugars and amino acids were proven to be inactive (Cohen and Bandurski 1982) while MeIAA is more potent when exogenously applied (Qin et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…From this point of view, the conversion from GA to Me-GA might be a part of a regulatory network for GA-ABA homeostasis during seed maturation and germination. The conjugation of phytohormones with methyl groups, sugars and amino acids has been proven as an effective way to regulate the phytohormones homeostasis in planta (Cohen and Bandurski 1982;Harris and Dugger 1986;Jackson et al 2001;Hou et al 2003;Qin et al 2005). For auxins, conjugates with sugars and amino acids were proven to be inactive (Cohen and Bandurski 1982) while MeIAA is more potent when exogenously applied (Qin et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…NCED proteins from other plant species were imported into the chloroplast (Iuchi et al, 2000;Qin and Zeevaart, 1999;Tan et al, 2001Tan et al, , 2003. A previous report suggested that, in the flavedo, the increases in ABA levels were associated with senescence and development of the chromoplast (Harris and Dugger, 1986). Rodrigo et al (2003) reported that ABA may play a role in the regulation of the rate of fruit coloration in citrus fruit because fruits of the ABAdeficient mutant exhibited a delay in the rate of degreening.…”
Section: Relationship Between Aba Accumulation and Gene Expression Ofmentioning
confidence: 99%
“…It has been reported that a small increase in abscisic acid and a large increase in its glucose ester were observed in the fruit exocarp during the natural color transition from green to orange. 5) This suggests that increased abscisic acid is converted to the glucose ester, which would be physiologically inactive. The glucose ester of abscisic acid would have a different role from that of the other terpenoid glycosides which have been isolated from citrus fruit peelings.…”
Section: + )-Abscisyl P-d-glucopyranoside Was First Isolated Frommentioning
confidence: 99%